Tradition and Transition: Feminine Selfhood in Nayantara Sahgal’s This Time of Morning. - SriAnnapoorni, D.; Jeyappriya, P. (Journal of Neonatal Surgery, 2025)
This Time of Morning (1965) by Nayantara Sahgal showcases detailed storytelling which investigates the reshaped traditional customs while investigating female identity transformation within independent India. The story takes place in Delhi during its developing political climate to depict women’s struggles between traditional customs and modern beliefs. Sahgal uses Rashmi and Nita to portray the various reactions between traditional female roles and personal yearnings which represent changing attitudes about women in India’s national era. Feminist and postcolonial theory by Simone de Beauvoir and Gayatri Chakravorty Spivak is used to analyze how the novel examines traditional female roles. The story presents Nita as an example of traditional obedience to family duties yet Rashmi stands as a heroine of independent self-expressiveness through her professional path. The study shows that Sahgal presents women in a complex way without idealization or simplistic portrayals yet she bases her depictions on real psychological elements together with specific contextual factors. Sahgal supports an active reorganization of cultural beliefs that responds to the transformations happening in society. The modern Delhi city serves simultaneously as an environmental environment as well as an emblematic area which rearranges individual and political character traits. Sahgal demonstrates empowerment through sophisticated female characters who use self-examination while creating space for bargaining to achieve their transformative goals. This Time of Morning continues to provide important insights into gender relations through its meaningful reinterpretation of cultural tradition which gives women leading roles in transformative processes. Through her compositions Sahgal provides essential knowledge about feminist literature by detailing an original approach to female self-identification and opposition within the Indian context.